2019
DOI: 10.1097/pq9.0000000000000192
|View full text |Cite
|
Sign up to set email alerts
|

Personal Phone Calls Lead to Decreased Rates of Missed Appointments in an Adolescent/Young Adult Practice

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…A review of 26 articles from diverse backgrounds found that patients who received a text notification were 23% less likely to miss their appointment than those who did not [ 42 ]. Similar results were obtained for personal phone calls in adolescents [ 39 ]. Text messages have been observed to produce similar outcomes to telephone calls, at a lower cost, in both adults [ 10 , 18 ] and pediatric patients [ 29 ].…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…A review of 26 articles from diverse backgrounds found that patients who received a text notification were 23% less likely to miss their appointment than those who did not [ 42 ]. Similar results were obtained for personal phone calls in adolescents [ 39 ]. Text messages have been observed to produce similar outcomes to telephone calls, at a lower cost, in both adults [ 10 , 18 ] and pediatric patients [ 29 ].…”
Section: Introductionsupporting
confidence: 86%
“…Lacy et al [ 26 ] identified three additional issues: emotional barriers (negative emotions about going to see the doctor were greater than the sensed benefit), perceived disrespect by the health care system, and lack of understanding of the scheduling system. In pediatric appointments, other reasons include caregiver’s issues, scheduling conflicts, forgetting, transportation, public health insurance, and financial constraints [ 11 , 19 , 23 , 39 , 44 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…These reminders are for record purposes to avoid unreasonable termination. This method is proven to significantly improve the appointment rate and reduce the number of missed appointments (Penzias et al, 2019). With proper appointment policies, reminders and patient's motivation, a missed appointment can be effectively controlled.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of missed dental appointments varied across studies between 9% to 40% (Awartani, 2003;Holtzman et al, 2013;Albaloushi and Da'ar, 2015;Storrs et al, 2016;Tandon et al, 2016). The most common excuse for missed dental appointments among patients was forgetfulness, busy with other matters and not brought by a parent for regular dental care (Tandon et al, 2016;Onyejaka et al, 2018;Kirby and Harris, 2019;Penzias et al, 2019). Factors that contributed to the missed dental appointments include age, gender and occupation status (Storrs et al, 2016;West et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Patient-related factors include forgetting the appointment, not receiving a reminder, emotional barriers, feeling disrespected by providers, and a lack of understanding of the scheduling system have emerged as common reasons cited by patients in previous research studies [24,30,20,37,28,1]. Additionally, transportation problems, work commitments, difficulties in taking time off from work, scheduling conflicts, issues related to health insurance, and financial concerns have been identified as significant factors influencing patients' ability to keep appointments [9,28,32]. Abu Lekham et al ( 2021) applied text mining to analyze the root causes of patient no-shows at an outpatient primary care medical organization serving rural areas in the Finger Lakes area of New York.…”
Section: Reasons For No-showsmentioning
confidence: 99%